Connection between the South and East Asian Monsoons: Comparing Summer Monsoon Rainfall of Pakistan and South Korea: Connection between the South and East Asian Monsoons: Comparing Summer Monsoon Rainfall of Pakistan and South Korea - Hussain, Mian Sabir; Abbas, Sohail; Shirazi, Safdar Ali; Khurshid, Mareena; Wahla , Saadia Sultan (International Journal of Economic and Environmental Geology, 2024)
This study investigates the tele-connection of the southeast Asian monsoon systems by comparing the summer monsoon (June to September) rainfall variability between Pakistan and south Korea. The daily data sets (1981- 2014) of rainfall of Pakistan and south Korea are utilized to explore the possible link. The data products of the National Centers for Environmental Prediction and National Center for Atmospheric Research (NCEP/NCAR) were also used for the understanding of the large-scale atmospheric environments. The patterns of summer monsoon rainfall on a daily basis between Pakistan and south Korea followed to each other throughout the year. Sub-seasonal differences of the summer monsoon revealed that July is the wettest month in both countries. The large-scale atmospheric environment of higher geopotential height revealed that the Tibetan high and the western north Pacific subtropical high are showing positive anomalies during positive phases over south Asia and east Asia, respectively. The anomalies of zonal wind are negative during positive phase and adverse in the negative phase between 20-40oN. The reduced westerly is interpreted as the seasonal variation and moving of jet streams from the east Asian route. The Tibetan high, northwestern Pacific subtropical high and the east Asian jet stream have reliable and sufficient linkage between the Pakistan and south Korea summer monsoon system.